Impacto de la inseminación artificial en vacunos de leche, en Chuquizongo – Usquil – Otuzco – La Libertad - Reyes Torres, Elva Noemi (2017)
The present research project aimed to determine the impact of artificial insemination on the productivity of milk cows in the village of Chuquizongo, in order to improve existing and low production creole breeds; improving the economy of breeders; Also, to identify the effective index of fertility in cows by artificial insemination (AI), to record the level of milk yield in cows by I.A. and calculate the benefit / cost of AI in dairy cows. The first historical indicator for cows was the interval between births ranged from 14.5 months. For heifers, weight and age at the first service was performed at 243.2 kg of live weight and 21.7 months, with the first calving age at 32.3 months. The bovine Creole, presents acceptable and comparable reproductive indexes to other pure breeds, although the breeding is carried out by breeders with scarce resources in conditions extreme height and poor quality of grasses. In order to improve these parameters, it is recommended to identify the problems that affect the individual reproductive performance of each cow, taking into account that the breeding system is dairy at stake, adopting the good use and interpretation of records by the producers in an orderly and practical manner to measure the reproductive efficiency of their herds and make the right decision